An Effort to Enhance Student Learning Outcomes through the Part Method Approach in the Physical Education, Health, and Recreation Study Program - Solissaa, Jonas (Andragogi: Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to improve student learning outcomes in swimming skills through the section method approach. The subjects of the study were students of the Physical Education, Health, and Recreation Study Program, Pattimura University, Ambon in 2024. This study used a Classroom Action Research (CAR) design with two action cycles. Data collection instruments included observation and performance tests of basic freestyle swimming technique skills assessed using a standardized assessment rubric. The results showed that the application of the section method approach contributed significantly to improving student learning outcomes. In cycle I, the learning completion rate reached 65%, where 14 out of 20 students successfully met the completion criteria. After improvements and optimization of the approach in cycle II, the completion rate increased to 100%, indicating that all students achieved the set successful standards. This increase reflects the effectiveness of the section method in improving students' basic swimming technique abilities. With the achievement of success indicators in cycle II, this study concludes that the section method can be used as an alternative effective learning strategy in developing students' basic swimming technique competencies. These findings are expected to be a reference for lecturers and physical education practitioners in optimizing the learning process, especially in water sports.